1998
DOI: 10.1017/s0022029998002921
|View full text |Cite
|
Sign up to set email alerts
|

Effect of decreased milking frequency of cows in late lactation on milk somatic cell count, polymorphonuclear leucocyte numbers, composition and proteolytic activity

Abstract: The effects of reducing the frequency of milking of cows in late lactation on milk somatic cell count (SCC), polymorphonuclear leucocyte (PMN) content, chemical composition and proteolytic activity were investigated. Intermittent milking is frequently practised by Irish farmers in late lactation, and the objective of this study was to determine whether this procedure could be linked to altered quality of milk. Seventeen Holstein Friesian cows in late lactation (>215 d in milk) were assigned to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
1
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 0 publications
6
37
1
4
Order By: Relevance
“…This was consistent with the findings of Salama et al (2003) in goats, Castillo et al (2008) in ewes and Lacy-Hulbert et al (1999) and Stelwagen et al (1994) in cows. Other studies have reported an increase in the SCC in cows subjected to ODM (Stelwagen and Lacy-Hulbert, 1996;Kelly et al, 1998). Although the SCC is not a precise indicator of inflammation, our data suggest that ODM does not induce a severe inflammatory reaction in the goat mammary gland, and this is also consistent with the limited permeability of secretory epithelium and limited tight junction disruption that had been observed with 36-h milking intervals .…”
Section: Discussionsupporting
confidence: 89%
“…This was consistent with the findings of Salama et al (2003) in goats, Castillo et al (2008) in ewes and Lacy-Hulbert et al (1999) and Stelwagen et al (1994) in cows. Other studies have reported an increase in the SCC in cows subjected to ODM (Stelwagen and Lacy-Hulbert, 1996;Kelly et al, 1998). Although the SCC is not a precise indicator of inflammation, our data suggest that ODM does not induce a severe inflammatory reaction in the goat mammary gland, and this is also consistent with the limited permeability of secretory epithelium and limited tight junction disruption that had been observed with 36-h milking intervals .…”
Section: Discussionsupporting
confidence: 89%
“…Based on the evidence described above, this system may explain also the effects of frequency and efficiency of udder emptying and the response in levels of milk secretion to the presence of bacterial infection of the udder. A direct association between decreased milking frequency and an increase in the activity of the PA-plasminogen-plasmin system has been found (Stelwagen et al, 1994;Kelly et al, 1998).…”
Section: Pa-pg-pl System and Hormonal Interrelationshipmentioning
confidence: 99%
“…Studies showed that improper feed management causes cows to compensate for the higher milk production and can result in lower recovery of body condition throughout lactation (Kelly et al, 1998;Smith et al, 2002). A well-balanced diet is essential to meet cow requirements and allow them the necessary intake for the recovery of body reserves throughout lactation.…”
Section: Itemmentioning
confidence: 99%
“…Implementing the third milking results in an increase in milk production, hence the cow requirements for feed supplements also increases. If supplementation is not done correctly, cows will have to supply nutrients from their body reserves to support the increased production, leading to weight loss and body condition score loss, which harm the whole metabolism (Kelly et al 1998;Smith et al, 2002).…”
Section: Itemmentioning
confidence: 99%
See 1 more Smart Citation